Hubungan Perawatan Tali Pusat dengan Kejadian Infeksi pada Bayi Baru Lahir di Wilayah Kerja Puskesmas Bontoa Kabupaten Maros - Qardhawijayanti, Suci; Hasriani, Siti; Asnuddin, Asnuddin; Nadima, Andi (Jurnal Sains, Teknologi dan Kesehatan, 2024)
Good and correct umbilical cord care will have a positive impact, namely the umbilical cord will fall off on the 5th and 7th day without any complications, while the negative impact of improper umbilical cord care is that the baby will experience neonatal tetanus. This study aims to determine the relationship between umbilical cord care and the incidence of infection in newborn babies at the Bontoa Community Health Center, Maros Regency. The type and research method used is the Cross Sectional Study method. The sample in this study was 34 mothers who had newborn babies at the Bontoa Community Health Center, Maros Regency, using a purposive sampling technique. The results of the study showed that 23 people (67.6%) were in the good umbilical cord care category, 6 people (17.6%) were adequate and 5 people (14.7%) were poor and 25 people had no infection. (73.5%) and 9 people (26.5%) experienced infection. There is a relationship between umbilical cord care and the incidence of infection with a value of ρ=0.002<from α=0.05, this means that Ho is rejected and Ha is accepted. It is best to carry out regular evaluations of umbilical cord detachment from both methods applied in the clinic, so that it is hoped that this can provide input in order to prevent prolonged umbilical cord detachment as an effort to prevent infection in babies.